William Torrey Harris papers - Harris, William Torrey, 1835-1909.
Chiefly drafts and printed copies of Harris's articles, addresses, lectures, and reports together with notes and printed material used in their preparation relating chiefly to the fields of education and philosophy. Subjects include duties of the primary and secondary school and the university; methods and courses of study; the benefits of studying Greek and Latin; benefits derived from education by men and women; the works of Ralph Waldo Emerson, Johann Wolfgang von Goethe, Georg Wilhelm Friedrich Hegel, and Herbert Spencer; function of the will in developing the "higher faculties of knowing"; immortality of the soul; and man's conception of the world. Includes annual reports he wrote as superintendent of schools of St. Louis, Mo. Also includes correspondence and manuscripts of his books.
Educator, author, editor, and philosopher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Emerson, Ralph Waldo, -- 1803-1882.; Goethe, Johann Wolfgang von, -- 1749-1832.; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Spencer, Herbert, -- 1820-1903.; St. Louis Public Schools (Saint Louis, Mo.); Education; Education -- Methodology; Education, Higher; Education, Primary; Education, Secondary; Educational psychology; Greek language -- Study and teaching; Immortality; Knowledge, Theory of; Latin language -- Study and teaching; Learning and scholarship; Men -- Education; Philosophy; Soul; Women -- Education; Authors; Editors; Educators; Philosophers